ANALISIS PELAYANAN PEMBUAT BERITA ACARA PEMERIKSAAN (BAP) BARANG ASSET DAERAH PADA PEGAWAI DI BIRO PERLENGKAPAN,UMUM DAN ASSET SEKRETARIAT DAERAH PROVINSI SULAWESI TENGAH - Iwan, Iwan (Katalogis, 2013)
This study aims at describing the services on the Making of Accounts on the Inspection of Goods and Local Assets. The method used was qualitative research. It was conducted from January to March 2012 and its location was on the Sub-Section of Maintenance and Goods Storage of the Bureau for General Supplies and Assets of Local Secretariat of Central Sulawesi Province. In order to obtain detail information from the target informants, purpose sampling technique was used. The informants were: the Head of Sub-Section of Maintenance and Storage, the Staff of Sub-Section of Maintenance, Storage, and Partnership. The source of data is primary and secondary. The techniques of data collection were observation, interview, and documentation. The data were analysed through data reduction, data display, and conclusion. It was found that the services system of the Bureau for General Supplies and Assets of Local Secretariat of Central Sulawesi Province was low because: the room for the services was dirty, the comfort for the publics was not under concern in term of protection toward the result of a particular service, and an agreement of reimbursement as the result of the service went wrong.